Exploring authenticity in performance : a comparative performance analysis of Arnold van Wyk’s Night Music for piano - Pinto Ribeiro, Bruno Alfredo (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MMus (Music))--University of Stellenbosch, 2009.